Manajemen Laktasi dan Kesejahteraan Ibu Menyusui - Wattimena, Inge; Werdani, Yesiana Dwi W.; Novita, Bernadette Dian; Dewi, D. A. Liona (Faculty of Psychology, Universitas Gadjah Mada, 2015)
A mother’s success of lactation depends on her self-management. This study aimed to reveal the contribution of self-awareness (introspection and observation) and self-determination (competency and autonomy) as self-management factors to a lactating mother’s well-being (self-actualization and positive mood). The subjects of this study were 100 mothers who had been breastfeeding for at least six weeks. A structured model was designed with self-awareness as an independent variable to dependent variable of well-being, and as an antecedent variable to self-determination affecting the dependent variable of well-being. Likert scale instruments were used. The data obtained from the questionnaires were analyzed using Structural Equation Modelling program. The models fitting the requirements showed that self-awareness had direct and indirect effects through self-determination on well-being, with a total effect of 0.924. It could be concluded that the success of lactation achieved through the self-management has a strong influence on well-being.